Dynamics of chaotic waves under weak nonlinear interaction in the magnetized plasma waveguide - Buts, V.A.; Manuilenko, O.V.; Tolstoluzhsky, A.P. (Вопросы атомной науки и техники, 2001)
The chaotic dynamics of high-frequency (HF) electromagnetic wave decay into HF electromagnetic waves and LF plasma waves in the magnetized plasma waveguide has been investigated. In contrast to [1-3], where we have investigated the case when one LF wave takes part in the interaction, in this work we consider the case when in the interaction a few of LF waves take part. It is shown that criterion of dynamic chaos occurence [1, 2] not only allows to qualitatively find the parameter region, where the dynamics of weak nonlinear wave interaction is chaotic, but also rather correctly describes the boundary of transition to chaos.